Outcome of Different Endometrial Preparation Protocols Prior to Frozen-Thawed Embryo Transfer on Pregnancy Outcomes in Women with Repeated Implantation Failure - Xiu YL; Sun KX; Zhang Q; Xiao YH; Bai X; Chen Y; Zhao MS; Yu YX (Dove Medical Press, 2023)
Yin-Ling Xiu, Kai-Xuan Sun, Qian Zhang, Yu-Hong Xiao, Xue Bai, Yong Chen, Meng-Si Zhao, Yue-Xin Yu Center of Reproductive Medicine, General Hospital of Northern Theatre Command, Shenyang, 110016, People's Republic of ChinaCorrespondence: Yue-Xin Yu, Center of Reproductive Medicine, General Hospital of Northern Theater Command, No. 83, Wenhua Road, Shenhe District, Shenyang, 110016, People's Republic of China, Tel +86-18809881296, Email yuyuexinpingan@163.comAim: To compare the pregnancy outcomes of frozen-thawed embryo transfer (FET) cycles among women with repeated implantation failure (RIF) treated with various endometrial preparation protocols.Methods: A total of 605 women with RIF were retrospectively recruited between January 2017 and December 2020 from Northern Theater General Hospital. Patients were divided into natural cycles, hormone replacement therapy (HRT) cycles, depot gonadotropin-releasing hormone (GnRH) agonist-HRT, and endometrial scratching (ES) plus depot GnRH agonist-HRT. The primary endpoint was clinical pregnancy rate, while secondary endpoints included live birth rate and pain assessment.Results: Of the 605 recruited patients, 63 were undergoing natural cycles, 281 were treated with HRT cycles, 141 treated with depot GnRH agonist-HRT, and 120 treated with ES combined with depot GnRH agonist-HRT. There were significant differences among protocols on clinical pregnancy rate (P=0.029), while no significant difference was observed among protocols on live birth rates (P=0.108). Multivariate analyses suggested that HRT (odds ratio [OR]: 0.50; 95% confidence interval [CI]: 0.28- 0.89; P=0.019) and depot GnRH agonist-HRT (OR: 0.49; 95% CI: 0.27- 0.91; P=0.021) cycles were associated with a lower clinical pregnancy rate as compared with natural cycles, while no significant difference between ES combined with depot GnRH agonist-HRT and natural cycles for clinical pregnancy rates (OR: 0.72; 95% CI: 0.38- 1.36; P=0.313). Moreover, the HRT (OR: 0.70; 95% CI: 0.39- 1.28; P=0.239), depot GnRH agonist-HRT (OR: 0.67; 95% CI: 0.35- 1.29; P=0.229), and ES combined with depot GnRH agonist-HRT (OR: 1.11; 95% CI: 0.58- 2.14; P=0.754) cycles had no significant effects on live birth rate as compared with natural cycles. A total of 87.50% patients treated with ES combined with depot GnRH agonist-HRT reported pain during the procedure.Conclusion: ES and depot GnRH agonists could be considered for RIF women with high-quality blastocysts, 14 days after verified transplantation failure.Keywords: endometrial scratching, depot GnRH agonist, repeated implantation failure, blastocysts, clinical pregnancy rate, live birth rate